EFEKTIFITAS DAN AKUNTABILITAS PENGELOLAAN PENDAPAT AN ASLI DAERAH BERBASIS AKUNTANSI AKRUAL YANG DIMODIFIKASI DI INDONESIA - Faris Mahdi (Journal of Management and Business, 2003)
Indonesian Local Governments have to finance their activities from their own effort. Realizing that there are many wealthy regions, but not slightly un-wealthy regions, it is important to think about effectiveness and accountability for Local Govemmenst to manage their asset to bring into real wealthy community.This article tries to give a few perspectives how to manage income for Local Government. It gives explanation about definition of income for Local Government, how they should be got and how they should be recorded under accrual base to become accountable, and how they should be used to measure effectiveness of Local Government activities.